Management of the Large Upper Eyelid Defects with Cutler-Beard Flap - Rahmi, Duman (Hindawi Publishing Corporation, 2014)
Background. To assess Cutler-Beard procedure results in patients after wide excision of malignant eyelid tumours. Materials and Methods. The records of two women and two men (four patients) referred to our clinic with eyelid mass complaints and malign eyelid tumour diagnosis according to the histopathological examination were examined retrospectively. Results. The patients were 60–73 years old and their average age was 66 ± 11.10. The follow-up period of the cases was 16 (6–25) months. Total excisional biopsy was applied to all patients and then Cutler-Beard full thickness lid reconstruction was done because of the wide localization of the tumour. The patients' diagnoses were consistent with basal cell carcinoma, sebaceous gland carcinoma, eyelid lymphoma, and squamous cell carcinoma. The patients' eyelids were separated from each other 1 month postoperatively with a second operation. Superior eyelid entropium and blepharochalasis were seen in one patient during followup. Conclusions. Cutler-Beard flap is a successful procedure for superior eyelid tumours accompanied by wide tissue loss. The long-time closure of the eyelids and the need for secondary surgery are the major disadvantages of this procedure. Our experience with this procedure will reveal better results with large case series.